Efisiensi Irigasi Kapiler Berbasis Capillary Mat pada Berbagai Jenis Sayuran Daun dengan Media Substrat Cocopeat dan Arang Sekam - Widya Andani; Ahmad Tusi; Elhamida Rezkia Amien; Sugeng Triyono (Jurnal Agricultural Biosystem Engineering, 2026)
Water scarcity and low surface irrigation efficiency are major constraints to leafy vegetable productivity in dryland farming. Capillary mat-based irrigation offers a solution through efficient water distribution to the root zone. This study aimed to analyze capillary irrigation efficiency using a cocopeat and rice husk charcoal mixture (1:1) on three leafy vegetables (pakcoy, lettuce, caisim), and to compare the effects of capillary mat lengths of 50% (M1) and 100% (M2) on water use efficiency and plant productivity. The experiment employed a Split-Plot Design within a Completely Randomized Design with three replications (18 experimental units). Measured parameters included environmental conditions (temperature, RH, VPD), nutrient quality (pH, EC, TDS), plant growth (height, leaf number, canopy area, root length, root fresh weight), yield (shoot fresh weight), water consumption, and water productivity.  The results showed that M2 provided a larger water supply than M1 but did not show a significant difference in water use efficiency. Average water productivity for M1 and M2 was 48.69 g/L and 49.86 g/L, respectively. Plant type influenced yield, with caisim producing the highest shoot fresh weight (92.3 g) under M2K3, while lettuce produced the lowest (38 g) under M1K2. Root parameters did not show a consistent interaction pattern between mat treatment and plant type. Economically, M1 was more efficient, with costs Rp10,640.00 lower per bed unit compared to M2. This study recommends using a 50% capillary mat (M1) for pakcoy and lettuce cultivation. Future research can be improved by selecting plants with uniform harvest periods, applying an automated microclimate control system, and utilizing high-precision water level sensors.